Impact Of Dividend Policy On The Value Of Firms - Nwaorgu, Innocent Augustine; Uzoegbu, Jennifer Nkeiruka (Archives of Business Research, 2018)
This study empirically investigates the impact of dividend policy on the value of firms for a sample of twelve (12) consumer and manufacturing companies listed on the Nigerian Stock Exchange (NSE). The study was carried out for a period of 10 years (2007-2016). The empirical estimation is based on the ‘Bird in Hand Dividend Theory’ supported by Fairchild (2010) and employed Random Effect Regression to analyze 120 observations. The results tend to support the theory of Miller and Modigliani (1961) which suggests that dividends are irrelevant to firm value for firms listed on the Nigerian Stock Exchange (NSE). Hence, from the empirical findings, the study concludes by agreeing with most of the dividend irrelevant proponents that dividend does not matter to corporate value. The study therefore carefully recommends that managers must review the opinions of their core investors in deciding dividend policy that meets with their expectations.